Psychotic Symptoms as the Initial Presentation of a Long-Lasting Misdiagnosed Anti-GAD65 Autoimmune Encephalitis: An Emblematic Case and Literature Review - Wang, Jianjun; Gong, Shenglan; Kong, Fanxin; Cai, Dongbin; Huang, Binqing; Zheng, Haotao; Lin, Songjun; Li, Jinfang; Zhang, Tianfeng (Frontiers in Psychiatry, 2022)
Objective: To present a long-lasting misdiagnosed case of anti-GAD65 autoimmune encephalitis (AE) and promote the early identification of reversible psychotic symptoms in AE. Methods: The case report was generated through detailed assessment of clinical characteristics, cerebral magnetic resonance images, and laboratory results. Meanwhile, a literatures review related to the topic was conducted. Results: Psychotic symptoms could be presented in the early stage of anti-GAD65 autoimmune encephalitis. Even though there exists a transdisciplinary gap that hinder the timely recognition of early psychiatric symptoms as components of organic disease, a few strategies could be introduced to enable the earlier recognition and appropriate treatment. Conclusions: Our report intends to raise awareness to promote the early identification of immune-mediated "symptomatic" forms of psychosis.